Trade liberalization in the Western Hemisphere - IDB (IDB WashingtonUS, 1995)
Focuses on the overall impact of hemispheric trade liberalization and on what kind of free trade agreements are desirable. Addresses key negotiating issues, deals with how to proceed toward a hemispheric free trade agreement and presents individual country perspectives.